Physicochemical properties and sensory attributes of herbal pastilles affected by the inclusion of Clitoria ternatea (L.) leaves - Ramlan, N.N.F.; Mohd Zin, Zamzahaila; Juhari, Nurul Hanisah; Smedley, K.L.; Mohd Zainol, Mohamad Khairi (Rynnye Lyan Resources, 2021)
Clitoria ternatea (L.) (Bunga Telang), is a well-known plant used as food colouring through its flowers. The plant’s leaves are also being used as medicinal ingredients to cure several diseases. However, the medicinal properties were not being explored extensively which could diversify the plant’s usage. The research was conducted on the inclusion of C. ternatea leaves to enhance the physicochemical properties and sensory acceptability of herbal pastille. Five different formulations of C. ternatea leaves pastille were developed with different percentages of C. ternatea leaves namely 2.5%, 5.0%, 7.5%, 10.0% and 12.5%. Physicochemical properties (antioxidant properties, colour profile, texture, moisture, sugar, fat, protein, ash, calorie and texture profile) and the sensory acceptability of C. ternatea leaves pastille was observed. The results show that the highest °Brix value was observed in sample D (74.20°) while water activity was higher in sample B (0.73). The analysis showed that the control sample exhibited a high hardness value (2641.70 N), springiness and cohesion values (0.87 N), gumminess value (2338.75 N), chewiness value (2089.71 N) and resilience value (0.44 N) to that of C. ternatea leaves herbal pastille. Sample E was found to contain a high TFA value (1.45), TPC value (23.32 GAE mg/g), and DPPH value (27.72%). Based on overall acceptance, the sensory analysis showed that the products were accepted by the panellists. Thus, the study revealed that the physicochemical properties of developed herbal pastille were being enhanced and found to be rich in antioxidants and accepted by the panellists.